Socio-cultural development of Omsk region districts as one of indicators of social sphere of modern Russia - I. A. Kostyuk (Омский научный вестник: Серия "Общество. История. Современность")
The success of the reforms in the society affecting all spheres depends on the ongoing changes in the social sphere, because the transformation is carried out by people who are able to consciously accept and implement them, and therefore to remain committed to tradition, accepting innovation as significant real values. It is in this aspect of socio-cultural activity generates social and cultural space, with the activity of the subject as a carrier and Creator of cultural values who can compete with cultural activities when all participants were predetermined by the passive role of spectator and participant in the best case, not a collective of the Creator of what is happening. The article deals with specific activities carried out in the municipalities of the Omsk region, implemented within the framework of the five directions of the state and regional policy in the socio-cultural sphere, as well as the traditions of individual municipalities that have incorporated the initiative and implemented the aspirations and talents of the villagers themselves